Reviving the strike: how working people can regain power and transform America - Burns, Joe (Brooklyn, NY, 2011)
"If the American labor movement is to rise again, it will not be as a result of electing different politicians, the passage of legislation, or improved methods of union organizing. Rather, workers will need to rediscover the power of the strike. Not the ineffectual strike of today, where employees meekly sit on picket lines waiting for scabs to take their jobs, but the type of strike capable of grinding industries to a halt—the kind employed up until the 1960s.